Upgraded hydrodissection and its safety enhancement in microwave ablation of papillary thyroid cancer: a comparative study - Zhen-Long Zhao; Ying Wei; Li-Li Peng; Yan Li; Nai-Cong Lu; Jie Wu; Ming-An Yu (International Journal of Hyperthermia, 2023)
AbstractObjectives To study the efficacy and safety of an improved hydrodissection protocol based on the perithyroidal fascial space during microwave ablation for papillary thyroid carcinoma (PTC).Methods The data of 341 patients (94 men and 247 women, median age 41 years old, 25%–75% interquartile range 34–53 years old, nodule maximum diameter 0.2–1.9 cm) who underwent microwave ablation for PTC were retrospectively reviewed. Among them, 185 patients underwent traditional hydrodissection and served as a control group, and 156 patients underwent improved hydrodissection based on perithyroidal fascial spaces, constituting the improved group. Improvements in safety were analyzed by comparing complications between the two groups. The characteristics of hydrodissected spaces, complications, and follow-up results were recorded.Results Hydrodissection was successfully performed in all enrolled patients according to the protocol. The incidence of hoarseness caused by recurrent laryngeal nerve injury, the most common complication in thermal ablation of thyroid nodules, was significantly lower in the improved group than in the control group (1.9% vs. 8.1%, p = 0.021). The median hoarseness recovery time in the improved group was shorter than that in the control group (2 months vs. 3 months, p = 0.032). During follow-up, no local recurrence was encountered in either group. The tumor disappearance rate was not significantly different between the two groups (69.9% vs. 75.7%, p = 0.228).Conclusions Improved hydrodissection based on perithyroidal fascial spaces had better protective effects than traditional hydrodissection.